The Metaverse and complex thinking: opportunities, experiences, and future lines of research - George-Reyes, Carlos Enrique; Peláez Sánchez, Iris Cristina; Glasserman-Morales, Leonardo David; López-Caudana, Edgar Omar (Frontiers in Education, 2023)
Research trends about the Metaverse have increased in recent years due to its potential to create immersive realities, where complex thinking becomes relevant as an ability to promote emerging ways to understand and explain the different realities that comprise a digital society. Although some investigations allow us to know both topics' concepts and applications, scientific literature production about them is scarce. In this work, we conducted a systematic review of the literature (SLR), analyzing 234 publications from various databases, including Scopus and Web of Science, to understand how studies about the Metaverse overlap with the components of complex thought. The results showed that there has been extensive exploration of the Metaverse since 2022. The prevalence of the Metaverse aligns with the design of algorithms and retail sales, and it primarily correlates with virtual reality technology. Likewise, various reference frameworks and taxonomies have been designed to explain the operation of the Metaverse in different formative spaces. We concluded that examining the Metaverse from the perspective of critical, systemic, scientific, and innovative thinking can open lines of research that affect the knowledge of immersive technologies and the evolution of disruptive digital ecosystems.